An inverse approach for estimating model-derived bubbly cavitation impact loads from target-zone vibrations with model-benchmark validation - Lihua Huang; Jingjun Yuan; Shun Zhang; Shuting Wan; Jiangyun Wang; Chuanqin Su; Tianyi Guan; Hongwei Xiao (Ocean Engineering, 2026)

LABLF: a multispectral and SAR image fusion method based on least squares-optimized adaptive box-guided and Laplacian-Gaussian filtering - Shuting Yang; Xunqiang Gong; Xiufang Zhou; Yichuang Luo; Yuting Wan; Ailong Ma; Yanfei Zhong (International Journal of Remote Sensing, 2026)

Entropy-Infused soft Sensing: A standpipe pressure feature modeling approach for Solid-Phase mass flux measurement in fluid catalytic cracking units - Lihua Huang; Zitong Zhang; Shuting Wan; Wei Peng; Jiafu Zhang; Zhonglin Ma; Mingxin Zhang (Fuel, 2026)

Multi-parameter fusion-based evaluation of cavitation intensity - Lihua Huang; Qiang Li; Shuting Wan; Jiangyun Wang; Jianxin Liu (Ocean Engineering, 2025)

New insights into the impact of heavy metals on phosphorus recovery: Interaction with the phase transition of CaP precipitation - Xiang Li; Xin Hu; Shuting Shen; Rui Wan; Guo Ting; Xiwu Lu (Journal of Environmental Chemical Engineering, 2025)

Mechanistic insights into heavy metal adsorption on hydroxyapatite: New perspectives from dynamic adsorption behavior - Shuting Shen; Wenjing Li; Ting Guo; Rui Wan; Xiwu Lu; Hongliang Dai; Xiang Li (Journal of Environmental Chemical Engineering, 2025)

Unravelling key factors controlling homogeneous crystallization during phosphorus recovery: From the perspective of crystallization kinetics - Xiang Li; Xin Hu; Shuting Shen; Rui Wan; Hongliang Dai; Xiwu Lu (Journal of Cleaner Production, 2025)

Urinary polycyclic aromatic hydrocarbon metabolites in Chinese pregnant women: Concentrations, variability, predictors, and association with oxidative stress biomarkers - Shuting Cao; Yanjian Wan; Yuanyuan Li; Shunqing Xu; Wei Xia (Science of The Total Environment, 2024)

Integrated transcriptome and SNP analysis reveals sex-related genetic insights in the black-spotted frog (Pelophylax nigromaculatus) - Xingyue Zhang; Gang Wan; Ziwei Li; Qiufu Wu; Shuting Xiong; Xiaoqing Wang; Lilang You; Yazhou Hu (Aquaculture International, 2024)

Bi2MoO6/MWCNTs-COOH/GCE electrochemical probe for ultrasensitively and selectively detecting antibiotic norfloxacin - Shuting Shi; Chuanqin Zhou; Aiting Chen; Nana Tang; Kun Wan; Youwei Jiang; Jun Liu; Quanguo He; Li Cao (Chemosphere, 2024)

Dynamic Changes of the Infralimbic Cortex and Its Regulation of the Prelimbic Cortex in Rats with Chronic Inflammatory Pain - Longyu Ma; Lupeng Yue; Shuting Liu; Yu Zhang; Meng Zhang; Shuang Cui; Feng-Yu Liu; Ming Yi; You Wan (Neuroscience Bulletin, 2024)
The prelimbic cortex (PL) is actively engaged in pain modulation. The infralimbic cortex (IL) has been reported to regulate the PL. However, how this regulation affects pain remains unclear. In the present study, we recorded temporary hyper-activity of PL pyramidal neurons responding to nociceptive stimuli, but a temporary hypo-function of the IL by in vivo electrophysiological recording in rats with peripheral inflammation. Manipulation of the PL or IL had opposite effects on thermal hyperalgesia. Furthermore, the functional connectivity and chemogenetic regulation between the subregions indicated an inhibitory influence of the IL on the PL. Activation of the pathway from the IL to the PL alleviated thermal hyperalgesia, whereas its inhibition exacerbated chronic pain. Overall, our results suggest a new mechanism underlying the role of the medial prefrontal cortex in chronic pain: hypo-function of the IL leads to hyperactivity of the PL, which regulates thermal hyperalgesia, and thus contributes to the chronicity of pain.

Sediment microbial fuel cell coupled floating treatment wetland for enhancing non-reactive phosphorus removal - Shuting Shen; Longxiao Xie; Rui Wan; Xiang Li; Xiwu Lu; Hongliang Dai (Chemosphere, 2024)

Research progress on portable electrochemical sensors for detection of mycotoxins in food and environmental samples - Youwei Jiang; Yingyu Sima; Lei Liu; Chuanqin Zhou; Shuting Shi; Kun Wan; Aiting Chen; Nana Tang; Quanguo He; Jun Liu (Chemical Engineering Journal, 2024)

Characterization, expression, and function analysis of AKR1A1 gene from yellow catfish (Tachysurus fulvidraco) - Long Yang; Shuting Zheng; Dan Kong; Shenghan Xiang; Jianfen Wu; Neng Wan; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2022)

Detection of pulmonary tuberculosis in children using the Xpert MTB/RIF Ultra assay on sputum: a multicenter study - Xiaoshan Peng; Qiong Liao; Min Fang; Yu Zhu; Yan Shi; Shuting Quan; Yacui Wang; Li Duan; Xiaomei Shi; Yang Liu; Manzhi Wang; Qingsong Wei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)